Corrosion Protection Studies of Crude Glycerol-Based Waterborne Polyurethane Coating on Steel Substrate. Issue 3 (10th December 2015) - Lee, Yuehlien; Luo, Xiaolan; Hu, Shengjun; Li, Yebo; Buchheit, Rudolph
Abstract : Crude glycerol, a low-value by-product from the biodiesel industry, has a significantly different composition compared to pure glycerol. Generally, crude glycerol contains various impurities, such as methanol, water, soap, free fatty acids, fatty acid methyl esters, and glycerides. In this study, waterborne polyurethane (WPU) coatings were prepared from crude glycerol-based polyols synthesized via a one-pot thermochemical conversion of crude glycerol. The corrosion properties of the coatings were characterized by electrochemical impedance spectroscopy, polarization measurements, and salt spray testing. The preliminary results showed that crude glycerol-based WPU coatings had a considerably enhanced corrosion resistant performance on metallic substrates.